2018
DOI: 10.1021/acs.est.7b05655
|View full text |Cite
|
Sign up to set email alerts
|

Copper Inhibition of Triplet-Induced Reactions Involving Natural Organic Matter

Abstract: The triplet excited state of natural organic matter (NOM*) is an important reactive intermediate in sensitizing transformation of a wide range of environmentally relevant organic compounds, but the impact of trace metals on the fate and reactivity of NOM* is poorly understood. In this study, we investigate the effect of low concentrations of copper onNOM*-mediated oxidation (electron transfer) and energy transfer reactions. The oxidative efficiency of NOM* from Suwannee River NOM (SRNOM) and the widely used mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 66 publications
8
46
0
Order By: Relevance
“…Further studies using complimentary techniques are needed to validate these findings, given the limitations of this study. It has been shown previously that NOM reactivity, via the formation of singlet oxygen, decreases in the presence of metals, 56,68,92 so the results of this study show that this decrease is not due to conformational changes affecting the ability of ground state oxygen to quench the excited triplet. We also showed that the analysis performed in this study, although very simplified, is applicable to both fluorescence quenching and enhancement interactions.…”
Section: Discussionsupporting
confidence: 60%
“…Further studies using complimentary techniques are needed to validate these findings, given the limitations of this study. It has been shown previously that NOM reactivity, via the formation of singlet oxygen, decreases in the presence of metals, 56,68,92 so the results of this study show that this decrease is not due to conformational changes affecting the ability of ground state oxygen to quench the excited triplet. We also showed that the analysis performed in this study, although very simplified, is applicable to both fluorescence quenching and enhancement interactions.…”
Section: Discussionsupporting
confidence: 60%
“…Phosphorescence quenching was mainly attributed to the following two reasons: (i) metal ion coordination disturbed the hydrogen bonds between the interdots, leading to destabilization of the triplet state and (ii) quenching of the excited triplet state due to the paramagnetic perturbations. 37 In addition, the developed CDs also showed strong binding ability to lanthanide ions. Tb 3+ and Eu 3+ ions were selected owing to their ladder-like energy levels and prominent luminescent performance.…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, the phosphorescence of CDs-4 was effectively quenched by Cu 2+ ions (Figure f). Phosphorescence quenching was mainly attributed to the following two reasons: (i) metal ion coordination disturbed the hydrogen bonds between the interdots, leading to destabilization of the triplet state and (ii) quenching of the excited triplet state due to the paramagnetic perturbations …”
Section: Resultsmentioning
confidence: 99%
“…Laboratory and field studies have also noted that a photosensitizer, such as natural organic matter (NOM), is typically required to initiate the formation of VOCs at the interface and may influence the concentration and identity of the VOCs produced. ,,, NOM is an important component of surface waters, present at concentrations between 0.1 and 20 mg L –1 , and is strongly enriched at the air–water interface, particularly when a microlayer is present. ,, In the aquatic environment, NOM is photochemically active due to the presence of chromophoric species, as it can act as a photosensitizer via its excited triplet state, and the excited triplet state also leads to the formation of different reactive intermediates such as singlet oxygen ( 1 O 2 ) and the hydroxyl radical (OH • ). Additionally, it has been reported that riverine and oceanic natural organic matter exhibit different photosensitizing properties, which are highly variable due to the intrinsic link with local geology and biology. In particular, the activity of marine natural organic matter shows even day to day variability, related to its origin and the sampling procedures used. , It has also been shown previously that the water composition, such as the presence of halides and different metals, alters the formation of the different reactive intermediates, thereby affecting the role that NOM plays in the photochemistry of surface waters. NOM can also participate in heterogeneous, light-induced reactions at the interface with trace gases, such as NO 2 , and ozone with chlorophyll .…”
Section: Introductionmentioning
confidence: 90%
“…In particular, the activity of marine natural organic matter shows even day to day variability, related to its origin and the sampling procedures used. 68,69 It has also been shown previously that the water composition, such as the presence of halides and different metals, alters the formation of the different reactive intermediates, [70][71][72][73][74][75][76] thereby affecting the role that NOM plays in the photochemistry of surface waters. NOM can also participate in heterogenous, light-induced reactions at the interface with trace gases, such as NO 2 , 51 and ozone with chlorophyll.…”
Section: Introductionmentioning
confidence: 90%